Australian sporting innovation: patently better? - Lloyd, M. (Sports Technology, 2011)
Australia has an enviable track record in sport, including achieving as high as fourth position in the summer Olympics medal table. But the role of sport in Australia is greater than this, and includes hosting of major sporting events and the economic contribution of sports, both locally and globally. Underpinning the importance of sport is sporting innovation, both home-grown and imported. Australia has had a long history of innovation in sport, be it the invention of Australian Rules Football in 1859, the winged keel used in the yacht Australia II and, more recently, smart sporting garments that give direct feedback to both users and their coaches. A useful means of tracking innovation in any area of sport is through patent filings. Modern innovators tend to file patents to protect their innovations, so reviewing published patents can provide valuable insight about new developments. In this study, we look at Australian patent filing data to identify overall trends in sporting innovation. This data show that the filing of sports-related patents in Australia is trending downwards overall, but the filing of Australian sources sports patents is relatively steady. This data are supported by a series of case studies of Australian sporting innovations and their intellectual property strategies, or lack of it thereof.